Gambaran Prokrastinasi Akademik Mahasiswa dan Implikasinya dalam Pelayanan Konseling - Sa’diah, Mifta Alimatul; Nurfarhanah, Nurfarhanah (ARZUSIN, 2024)
This research is motivated by the existence of academic procrastination that occurs among students. Students carry out high academic procrastination because students do not have the ability to manage their time well and prefer to do more enjoyable tasks than completing tasks. This study aims to describe the academic procrastination of curriculum and educational technology students and its effectiveness in counseling services. This type of research is quantitative research with a descriptive method. The population in this study was 436 students with a research sample of 209 students of the Curriculum & Educational Technology Department who were active in lectures in the 2020, 2021, 2022, and 2023 classes of the 2024/2025 academic year. The sampling technique for this study used the Proportional Stratified Random Sampling technique. Data collection was carried out through the use of instruments using a Likert scale, namely using academic procrastination instruments for students. The results of this study indicate that: (1) the level of academic procrastination of students majoring in curriculum and educational technology as a whole is in the moderate category. (2) the level of academic procrastination of students based on aspects of being stuck in starting and completing tasks is in the moderate category. (3) the level of academic procrastination of students based on aspects of being late in completing tasks is in the moderate category. (4) the level of academic procrastination of students based on aspects of time discrepancies between plans and actual performance is in the moderate category. (5) the level of academic procrastination of students based on aspects of doing more enjoyable activities is in the moderate category. Based on the results of this research, counselors can provide assistance to students to reduce the level of academic procrastination of students in the form of: information services, individual counseling services, group guidance services and group counseling services.